Landscape Fragmentation in Iceland - Einar Hjörleifsson 1984- (2014)
Landscape fragmentation measurements provide baseline data of direct human influence on landscape and habitat systems through land use. In 2011, the European Environment Agency, the EEA and the Swiss Federal Office for the Environment or FOEN created a comprehensive report on the status of landscape fragmentation in 28 European countries, excluding Iceland. This thesis builds on EEA and FOEN methodology in order to create comparable data for Iceland. The Icelandic data set had to be adjusted to the European format to ensure that the results could be compared. The calculations were obtained using GIS software technology, where five types of reporting units were used with six different fragmentation geometries. Three of the six fragmentation geometries were created considering local environmental factors, amending the constraining factors used in the European research. The results indicate that landscape fragmentation in Iceland is low. By revealing the baseline data now, one can account for fragmentation in future infrastructure development planning through monitoring. This can be achieved on a country level e.g. by implementing the base line indicators as one of the factors considered in the newly proposed country planning policy. The effects of fragmentation to ecosystems accrue in a gradual manner. Addressing the issue beforehand can limit costly mitigation measures in the future and furthermore strengthen Iceland’s ability to provide various landscape habitats to the country´s particular flora and fauna. Sundrun landslagsheilda er það þegar stórum landslagssvæðum er skipt upp í minni og einangraðari svæði (EEA & FOEN, 2011). Helstu áhrifaþættir eru mannlegir þættir eins borgvæðing sem og línulegir þættir eins og lestarteinar og vegir. Sundrun landslags hefur margvísleg áhrif á búsvæða lífvera, þar sem þau bæði skerðast en einnig breytast að innri gerð. Umhverfisstofnun Evrópu og Umhverfisstofnun Sviss reiknuðu megindlega hver sundrun landslagsheilda væri innan 28 landa í Evrópu (EEA & FOEN, 2011) og ...